So, I have this proof:

Let a be an open sentential variable. Let K and C be prepositional variables asserted of sentences.


  1. K(a) <=> C(a) & a
  2. C(a) <=> C( C(a))
  3. C(a & b) <=> C(a) & C(b)


  1. K(a)


  1. C(a) & a //by 1,4
  2. C( C(a)) //by 2,5
  3. C( C(a)) & C(a) //by 5,6
  4. C( C(a) & a) //by 3,7
  5. C( K(a)) //by 1,8
  6. C( K(a)) & K(a) //by 4,9
  7. K( K(a)) //by 1,10


  1. K(a) -> K( K(a))
  2. K( K(a)) -> K(a) //by 1

And so

  1. K(a) <=> K( K(a)) //by 12,13


Can anyone see any issues with this? The thing that I'm least sure about is the use of recursive.


  • PS: You let K and N be propositional variables, then used K and C in the proof. Sep 23 '18 at 13:09

It is correct, but you've skipped over some steps, which obsured your reasoning.

For instance step 13. You just say K(K(a)) → K(a) by 1. Why?

Well, indeed, applying 1 gives you K(K(a)) ↔ C(K(a)) & K(a) and you can obtain the desired result from that, but you should spell this out. Show your working more.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.